Analysis of Cell Saver use and mortality in liver transplant - David, André Ibrahim (2017)
Introduction: Liver transplantation is considered the best treatment for irreversible liver disease. Due to the complexity of the procedure generally multiple blood transfusions are required. One option to reduce this need is the use of Cell Saver providing blood cell recovery and reinfusion. Purpose: to evaluate mortality in the number of washed red blood cell units recovered by Cell Saver and perioperative mortality. Methods: Data collection of transplant patients using CellSaver on the period from July 2014 to February 2017. Results: Performed 56 liver transplants, the diagnosis prevalent was liver cirrhosis by hepatitis C virus (37,5%). Of these 45 (80,4%) of the transplants used Cell Saver, which had a median MELD of 24,5 (range 7-50). Taking into account the use of Cell Saver in washed red blood cell units and recovered notes a median of four (range 1-45). 12 died (26,7%), the average of these MELD was 25,5 (range 1-50) and the use of washed red blood cell and recovered was a median of 4,5. Conclusion: Patients who died used a similar amount of washed and recovered erythrocyte units.